ANALISIS PENERAPAN ISAK 35 PADA PANTI ASUHAN DORKAS - Sembiring, Andry (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
The purpose of this study is to greatly assess how much Dorkas Orphanage follows the Financial Accounting Standards (ISAK) 35 in preparing its financial statements. As a non-profit organization, the orphanage has more difficulty in providing consistent, clear and responsible financial statements. In this study, a case study method and data collection through interviews, observations and documentation of the orphanage’s administration are used. According to the research findings, lack of understanding of the accounting standards and lack of training are the major participations for the implementation of ISAK 35. Therefore, to improve accounting expertise and external support so that the orphanage can produce financial statements that meet the standards and increase public confidence are required.